2001
DOI: 10.1073/pnas.191268798
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of an influenza virus promoter and their implications for viral RNA synthesis

Abstract: The influenza A virus, a severe pandemic pathogen, has a segmented RNA genome consisting of eight single-stranded RNA molecules. The 5 and 3 ends of each RNA segment recognized by the influenza A virus RNA-dependent RNA polymerase direct both transcription and replication of the virus's RNA genome. Promoter binding by the viral RNA polymerase and formation of an active open complex are prerequisites for viral replication and proliferation. Here we describe the solution structure of this promoter as solved by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 39 publications
4
91
1
Order By: Relevance
“…The structures of vRNA and cRNA promoter regions have been determined by NMR. [103][104][105] Although they show structural similarities, some marked differences are also apparent, that could account for their differential recognition by the virus polymerase. In fact, biochemical and genetic evidences suggest that distinct regions of the polymerase interact with vRNA or cRNA promoter regions.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The structures of vRNA and cRNA promoter regions have been determined by NMR. [103][104][105] Although they show structural similarities, some marked differences are also apparent, that could account for their differential recognition by the virus polymerase. In fact, biochemical and genetic evidences suggest that distinct regions of the polymerase interact with vRNA or cRNA promoter regions.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Scalar 1 J CH and dipolar 1 D CH couplings were derived from natural abundance 1 H- 13 C HSQC experiments with and without Pf1 (ϳ10 mg/ml) at 30°C. Pf1 filamentous bacteriophage was purchased from ASLA, Ltd. Alignment tensor analysis of the observed residual dipolar couplings was performed as described previously (20). All structure calculations were performed by crystallography and NMR system (CNS) software (21).…”
Section: Methodsmentioning
confidence: 99%
“…i) The structure of the viral promoters: Through the use of Nuclear Magnetic Resonance (NMR) and calculations for determining the 3D structure of the vRNA promoter, it has been shown that the vRNA promoter has a terminal stem, followed by an internal loop, and a proximal stem [81][82]. The terminal stem displays an inherent bend that allows the viral promoter to be easily melted, therefore possibly playing a regulatory role during the initiation of RNA synthesis [82].…”
Section: Knowing When To Stop and Accelerate Leads To A More Pathogenmentioning
confidence: 99%
“…The terminal stem displays an inherent bend that allows the viral promoter to be easily melted, therefore possibly playing a regulatory role during the initiation of RNA synthesis [82]. This intrinsic bending of the terminal stem might be of great relevance for transcription initiation, since the viral RdRp does not appear to have a helicase activity associated to it [82].…”
Section: Knowing When To Stop and Accelerate Leads To A More Pathogenmentioning
confidence: 99%
See 1 more Smart Citation